H3K27me3 expression and methylation status in histological variants of malignant peripheral nerve sheath tumours. Issue 2 (1st September 2020) - Lyskjær, Iben; Lindsay, Daniel; Tirabosco, Roberto; Steele, Christopher D; Lombard, Patrick; Strobl, Anna‐Christina; Rocha, Ana M; Davies, Christopher; Ye, Hongtao; Bekers, Elise; Ingruber, Julia; Lechner, Matt; et al.
Abstract: Diagnosing MPNST can be challenging, but genetic alterations recently identified in polycomb repressive complex 2 (PRC2) core component genes, EED and SUZ12, resulting in global loss of the histone 3 lysine 27 trimethylation (H3K27me3) epigenetic mark, represent drivers of malignancy and a valuable diagnostic tool. However, the reported loss of H3K27me3 expression ranges from 35% to 84%. We show that advances in molecular pathology now allow many MPNST mimics to be classified confidently. We confirm that MPNSTs harbouring mutations in PRC2 core components are associated with loss of H3K27me3 expression; whole‐genome doubling was detected in 68%, and SSTR2 was amplified in 32% of MPNSTs. We demonstrate that loss of H3K27me3 expression occurs overall in 38% of MPNSTs, but is lost in 76% of histologically classical cases, whereas loss was detected in only 23% cases with heterologous elements and 14% where the diagnosis could not be provided on morphology alone. H3K27me3 loss is rarely seen in other high‐grade sarcomas and was not found to be associated with an inferior outcome in MPNST. We show that DNA methylation profiling distinguishes MPNST from its histological mimics, was unrelated to anatomical site, and formed two main clusters, MeGroups 4 and 5. MeGroup 4 represents classical MPNSTs lacking H3K27me3 expression in the majority of cases, whereas MeGroup 5 comprises MPNSTs exhibiting non‐classical histology and expressing H3K27me3 and cluster with undifferentiated sarcomas. The two MeGroups are distinguished by differentially methylated PRC2‐associated genes, the majority of which are hypermethylated in the promoter regions in MeGroup 4, indicating that the PRC2 target genes are not expressed in these tumours. The methylation profiles of MPNSTs with retention of H3K27me3 in MeGroups 4 and 5 are independent of mutations in PRC2 core components and the driver(s) in these groups remain to be identified. Our results open new avenues of investigation. © 2020 The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd. on behalf of The Pathological Society of Great Britain and Ireland.